Income differences and prices of tradables - Ina Simonovska (University of California, Department of Economics, 2010)
This paper presents novel evidence of price discrimination, using prices of identical goods in 28 countries. I explain the observed phenomenon via non-homothetic preferences, in a model of trade with product differentiation and firm productivity heterogeneity. The model brings theory and data closer along a key dimension: it generates positively related prices of tradables and income, while preserving exporter behavior and trade flows of existing frameworks. It further captures observations that richer countries buy more per product and consume more diverse bundles. Quantitatively, the model suggests that variable mark-ups account for 80% of the positive price-income relationship across 123 countries.
Keywords: E31; F12; L11; 330; pricing-to-market; PPP; heterogeneous firms; non-homothetic preferences; Betriebliche Preispolitik; Preisdifferenzierung; Produktivität; Offenbarte Präferenzen; Internationaler Preiszusammenhang; Welt